2016
DOI: 10.1002/bdm.1962
|View full text |Cite
|
Sign up to set email alerts
|

Should Versus Want: On the Relative Contribution of Injunctive Norms and Preferences on Trust Decisions

Abstract: Despite much research on the determinants of trust among strangers, its mechanisms are understood only rudimentarily. Recently, it has been proposed that people trust strangers because they believe they should, thus complying with an injunctive norm even if it conflicts with their preferences. However, given the boldness of this claim and in light of independent arguments and earlier findings that suggest otherwise, the hypothesis requires critical scrutiny. Thus, we tested whether the decision to trust (in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…It is also unclear if people trust primarily because it is what they feel they should do. Consistent with the idea that trust is not exclusively moral, Thielmann and Hilbig (2017) found that ratings of what people want to do were a stronger predictor of trust behavior compared with feelings of obligation. These findings point to the idea that trust is also influenced by instrumental concerns (see also Evans & Krueger, 2016 )—people trust, in part, because they hope to gain something from the interaction.…”
Section: Perceptions Of Morality Sociability and Competencesupporting
confidence: 56%
See 1 more Smart Citation
“…It is also unclear if people trust primarily because it is what they feel they should do. Consistent with the idea that trust is not exclusively moral, Thielmann and Hilbig (2017) found that ratings of what people want to do were a stronger predictor of trust behavior compared with feelings of obligation. These findings point to the idea that trust is also influenced by instrumental concerns (see also Evans & Krueger, 2016 )—people trust, in part, because they hope to gain something from the interaction.…”
Section: Perceptions Of Morality Sociability and Competencesupporting
confidence: 56%
“…We consider three central hypotheses: First, we ask if generalized trust is associated with perceptions of morality. Work on principled trustfulness posits that people perceive trust in moral terms ( Dunning et al, 2014 ), but other findings suggest that trust occurs for more self-interested reasons ( Evans & Krueger, 2016 ; Thielmann & Hilbig, 2017 ). Second, we ask if generalized trust is associated with perceptions of sociability.…”
Section: Studymentioning
confidence: 99%
“…Participants completed the neuroticism and conscientiousness subscales (containing 17 items) drawn from the Chinese version of the Big Five Inventory‐44 (John, Donahue, & Kentle, ; John, Naumann, & Soto, ). Altruism was assessed with the DG, and the threshold for unfairness was measured by the UG (Forsythe, Horowitz, Savin, & Sefton, ; Thielmann & Hilbig, ). The mean UG scores were calculated using willingness circled on a 6‐point scale, and dictator allocations of 100 yuan made by participants in DG were coded.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, people trust less when their ego has been depleted and they miss the self-control to do what is morally right (Ainsworth, Baumeister, Ariely, & Vohs, 2014). To be sure, what people want to do is also a high correlate of trust (Thielmann & Hilbig, 2017), but beyond that our studies suggest that rates of trust are pushed beyond the levels suggested by economics because of people’s beliefs about what they should do in trust situations (Dunning et al, 2014).…”
Section: Observations Of Trustmentioning
confidence: 51%